PROGESTERONE AND ESTRADIOL PROFILES DURING ESTROUS CYCLE AND GESTATION IN DWARF GOATS (CAPRA HIRCUS) - S. A. KHANUM, M. HUSSAIN AND R. KAUSAR (Pakistan Veterinary Journal, 2008)
Serum progesterone and estradiol profiles during estrous cycle, gestation and parturition in four Dwarf goat females (Capra hircus) were monitored. Blood sampling was carried out daily during estrous cycle and on alternate days during gestation till parturition. Observations regarding length of estrous cycle, gestation length, litter size and birth weight of kids were recorded. With the initiation of cyclicity, estradiol attained higher levels (7.7 ± 1.7 pg/ml) at estrus phase and dropped down to the lower levels within 3 to 4 days post-estrus. Concomitantly, progesterone started to increase from the mean basal value of 0.1 ± 0.03 ng/ml on day-0 to 3.0 ± 0.9 ng/ml on day-6 of estrous cycle and reached the peak value of 7.7 ± 0.6 ng/ml on day-12. From day-15, a decline was observed in progesterone values till the end of the cycle. A second estradiol rise of 14.0 ± 1.2pg/ml was observed on day-18 of the cycle. The mean estrous cycle length was 18.2 ± 2.1 days. During gestation, higher progesterone levels were maintained in the range of 4.3–11.0 ng/ml. Estradiol remained at lower concentrations for 30-50 days of gestation, then gradually increased and reached 270 ± 13.0 pg/ml a few days before parturition. It dropped again to basal values within 1-2 days postpartum. The mean gestation length in Dwarf goats was 144.8 ± 3.9 days and the litter size was 1.8 ± 0.5. It was concluded that Dwarf goat is a prolific breed, having a short gestation length with multiple births being common.